Ketika kekerasan dianggap seksi: persepsi laki-laki bahwa perempuan suka kekerasan memicu pola pikir ekstremis militan - Arifin, Haykal Hafizul; Lamuri, Aly; Rizkiyatsa, Arga; Kurniawan, Aryodi Wahyu; Nurmala, Sukma (Jurnal Psikologi Sosial, 2024)
Inspired by the paradigm of mate selection motives in evolutionary psychology, this research seeks to determine the extent to which violent extremist thought patterns are a product of perceptions of attractiveness that persist in men as a response to intrasexual selection. The survey was conducted on 192 samples of the general population in Indonesia, on a male sample (n = 80), after controlling for demographic variables, including dark personality (dark triad), men's subjective perception that Indonesian women find violence attractive (PAOSV) predicts militant-extremist mindset. PAOSV was the only variable that predicted violent extremism mindset in men. Furthermore, we discovered a mechanism that we call “sexualization of violence” – namely the extent to which individuals perceive violence as sexy, manly, and cool (AV) as a process that arises from the perception of high levels of positive feedback from the opposite sex towards violence. Where in the sample of men in this study, the only variable that shaped the mindset of violent extremism was sexual motives. The discussion elaborate differences in perceptions of attraction to violence between men and women, differentiation and gaps in perceptions between men and women in assessing violence. This study has practical implications, namely discussing the importance of the role of women as active agents in the formation of a culture of nonviolence.